Routledge Handbook of International Sport Business 2017
DOI: 10.4324/9781315709635-5
|View full text |Cite
|
Sign up to set email alerts
|

Major Sport Events at the Centre of International Sport Federations’ Resource Strategy

Abstract: Trotz deutrcher Nörgelei-Die Oillit¿ from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This new environment has influenced the identity of IFs, which have become increasingly professional and commercial since the end of the 20th century. More specifically, the Olympic IFs started to realize the commercial value of their major events and of broadcasting and logo/naming rights, over which they have begun to assert ownership (Clausen and Bayle, 2017 ). According to Zeimers et al ( 2021 ), this new operating environment has resulted in IFs becoming hybrid organizations whose sporting role is increasingly accompanied by commercial objectives, which they try to counterbalance by undertaking social initiatives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This new environment has influenced the identity of IFs, which have become increasingly professional and commercial since the end of the 20th century. More specifically, the Olympic IFs started to realize the commercial value of their major events and of broadcasting and logo/naming rights, over which they have begun to assert ownership (Clausen and Bayle, 2017 ). According to Zeimers et al ( 2021 ), this new operating environment has resulted in IFs becoming hybrid organizations whose sporting role is increasingly accompanied by commercial objectives, which they try to counterbalance by undertaking social initiatives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since they first came into being at the beginning of the 20th century, international sport federations (hereafter IFs) have evolved from volunteer-run associations to highly professional organizations, the largest of which (e.g., FIFA) employ up to 700 staff (Clausen and Bayle, 2017 ). Although an IF's primary role is to develop its sport internationally (see Clausen and Bayle, 2017 ; Clausen et al, 2018 ), many IFs are becoming increasingly business-oriented and are commercializing their major events. For some IFs, organizing events has become a core activity and a true business involving numerous commercial partners, such as sponsors, broadcasters, and marketing agencies.…”
Section: Introductionmentioning
confidence: 99%
“…With the Tokyo 2020 Olympic Games postponed until 2021, then subsequently declared a crowd-free event, the financial cost is monumental. Clausen and Bayle (2017) noted the centrality of major sport events to the resource strategies of IFs. They concluded that, … events are a necessary prerequisite for federations to attract sponsors, potential buyers of broadcasting and commercial rights.…”
Section: New Stakeholders Emerging Issuesmentioning
confidence: 99%
“…Contemporary International Sport Federations (IFs) are not only custodians of their sport's policies, rules and regulations, but they also manage business activities such as major international sport events (Clausen & Bayle, 2017) and commercial contracts (Cornelissen, 2010). The changing nature of sport can be seen in national sport federations (NFs) through to sport clubs (Girginov & Sandanski, 2008;Skinner, Stewart, & Edwards, 1999).…”
Section: Introductionmentioning
confidence: 99%